2023
DOI: 10.1038/s41467-023-39809-3
|View full text |Cite
|
Sign up to set email alerts
|

Probing hyperbolic and surface phonon-polaritons in 2D materials using Raman spectroscopy

Abstract: The hyperbolic dispersion relation of phonon-polaritons (PhPols) in anisotropic van der Waals materials provides high-momentum states, directional propagation, subdiffractional confinement, large optical density of states, and enhanced light-matter interactions. In this work, we use Raman spectroscopy in the convenient backscattering configuration to probe PhPol in GaSe, a 2D material presenting two hyperbolic regions separated by a double reststrahlen band. By varying the incidence angle, dispersion relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Varying the pump–probe time delay allows building movies of species propagation over femtoseconds–nanoseconds and nanometers–micrometers. Although there are many processes through which optical excitation can excite low-frequency PhPs, , the Raman spectra displayed in Figures e and S3 suggest that interlayer exciton–phonon interactions in our heterostructures promote excitation of upper reststrahlen PhPs primarily through a resonant Raman process. We further posit that the presence of pump-generated PhPs in hBN locally modifies the dielectric function of the heterostructure.…”
mentioning
confidence: 89%
“…Varying the pump–probe time delay allows building movies of species propagation over femtoseconds–nanoseconds and nanometers–micrometers. Although there are many processes through which optical excitation can excite low-frequency PhPs, , the Raman spectra displayed in Figures e and S3 suggest that interlayer exciton–phonon interactions in our heterostructures promote excitation of upper reststrahlen PhPs primarily through a resonant Raman process. We further posit that the presence of pump-generated PhPs in hBN locally modifies the dielectric function of the heterostructure.…”
mentioning
confidence: 89%
“…Initial works demonstrated resonant Raman spectroscopy as a valuable tool to probe PhP modes at Van der Waals (VdW) material interfaces, revealing effects such as Raman activity of silent phonons 26 , enhancement of PhP Raman features 27 , and PhPs outside the Reststrahlen band 28 . Further, recent investigations have shown that conventional backscattering Raman can probe PhP modes in 2D gallium selenide, utilizing the polarizability selection rules 29 . Such techniques are not restricted to 2D materials, micro-Raman investigations of 4H-SiC nanopillars found that spatial dispersion of the permittivity in dielectric nanostructures can play a major role in the spectral behavior of PhPs 20 .…”
Section: /11mentioning
confidence: 99%
“…The basis for our approach comes from the polarizability selection rules, which have been used to calculate the Raman scattering intensities of propagating PhP modes in VdW materials 29 . We modify this approach to make it more suitable for describing localized SPhPs in nanostructures by expressing the Raman response of the nanostructure in terms of its resonant eigenmodes.…”
Section: Field Mapping Theorymentioning
confidence: 99%
“…1,2 Despite the advent of novel targeted therapies and immunotherapies aimed at enhancing cancer survival rates, lung cancer mortality continues to rise. 3 Characteristically, lung cancer remains largely undetected in its nascent stages, often manifesting symptoms only at its most aggressive phase. 4 The imperative for early diagnosis cannot be overstated as it facilitates the timely detection and treatment of lung cancer, thereby curtailing disease progression and reducing mortality rates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lung cancer is a serious threat to human life and health and has become one of the leading cause of cancer-related fatalities globally. , Despite the advent of novel targeted therapies and immunotherapies aimed at enhancing cancer survival rates, lung cancer mortality continues to rise . Characteristically, lung cancer remains largely undetected in its nascent stages, often manifesting symptoms only at its most aggressive phase .…”
Section: Introductionmentioning
confidence: 99%